Nanoparticle-based immunotherapy of pancreatic cancer - Noubissi Nzeteu, Gaetan Aime; Gibbs, Bernhard F.; Kotnik, Nika; Troja, Achim; Bockhorn, Maximilian; Meyer, N. Helge (Frontiers in Molecular Biosciences, 2022)
Pancreatic cancer (PC) has a complex and unique tumor microenvironment (TME). Due to the physical barrier formed by the desmoplastic stroma, the delivery of drugs to the tumor tissue is limited. The TME also contributes to resistance to various immunotherapies such as cancer vaccines, chimeric antigen receptor T cell therapy and immune checkpoint inhibitors. Overcoming and/or modulating the TME is therefore one of the greatest challenges in developing new therapeutic strategies for PC. Nanoparticles have been successfully used as drug carriers and delivery systems in cancer therapy. Recent experimental and engineering developments in nanotechnology have resulted in increased drug delivery and improved immunotherapy for PC. In this review we discuss and analyze the current nanoparticle-based immunotherapy approaches that are at the verge of clinical application. Particularly, we focus on nanoparticle-based delivery systems that improve the effectiveness of PC immunotherapy. We also highlight current clinical research that will help to develop new therapeutic strategies for PC and especially targeted immunotherapies based on immune checkpoint inhibitors.